Process Analysis and Trial Tests for Hot-Rolled Stainless Steel/Carbon Steel Clad Plates - Chen, Z.Y.; Li, J.X.; Lin, Z.G.; Qi, J.J.; Sun, L.; Wang, G.D. (Проблемы прочности, 2019)
The trials of 304 stainless steel-clad plate made of plain Q345B carbon steel were performed on hot-rolling line of the Hesteel Group. After the two runs of pilot production, the key process parameters for the stainless steel/carbon steel clad plate were found to meet the GB/T 8165-2008 requirements. The interface shear strength of the clad plate was higher than 360 MPa, the yield strength of the final product was over 257 MPa, the clad plate tensile strength and elongation exceeded 351 MPa and 39.8%, respectively. The interpenetration of stainless steel and plain carbon steel layers was established to be complete, with the adequate composite interface. The tensile and shear properties of stainless steel-clad plates produced by the rolling process were at the same level as those obtained via the explosive method as an alternative, while their production cost were somewhat reduced. Проведено промышленное испытание листа, плакированного нержавеющей сталью 304 с обычной углеродистой сталью Q345B, с использованием линии горячей прокатки группы Hesteel. После двух этапов опытного производства было установлено, что основные техниРефераты ческие показатели производства листа удовлетворяют требованиям GB/T 8165 2008. Прочностьпри сдвиге на поверхности раздела плакированного листа превышала 360 МПа, предел текучести конечного продукта превышал 257 МПа, прочность при растяжении испытуемого материала превышала 351 МПа, а удлинение плакированного листа превышало 39,8%. Показано, что степень амальгамации слоя нержавеющей стали и нелегированной углеродистой стали была высокой, а поверхность раздела композита ровной и совершенной. Свойства при растяжении и сдвиге плакированных нержавеющей сталью листов, изготовленных с помощью процесса взрывной прокатки, соответствовали таковым, изготовленным путем взрывного процесса. Однако эффективность процесса взрывной прокатки существенно выше, чем взрывного процесса, при этом производственные затраты были гораздо меньше. Проведено промислове випробування листа, плакованого нержавіючої сталлю 304 зі звичайною вуглецевою сталлю Q345B, з використанням лінії гарячої прокатки групи Hesteel. Після двох етапів дослідного виробництва було встановлено, що основні технічні показники виробництва листа задовольняють вимогам GB/T 8165-2008. Міцність при зсуві на поверхні розділу плакованого листа перевищувала 360 МПа, межа плинності кінцевого продукту перевищував 257 МПа, міцність при розтягузі випробуваного матеріалу перевищувала 351 МПа, а подовження плакованого листа перевищувало 39,8%. Показано, що ступінь амальгамування шару нержавіючої сталі і нелегованої вуглецевої сталі була високою, а поверхня розділу композиту рівною і досконалою. Властивості при розтязі і зсуві плакованих нержавіючої сталлю листів, виготовлених за допомогою процесу вибуховий прокатки, відповідали таким, виготовленим шляхом вибухового процесу. Однак ефективність процесу вибуховий прокатки істотно вище, ніж вибухового процесу, при цьому виробничі витрати були набагато менше.